(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
According to the 2011 census, this industry employs 54.6% of the country’s workers. Furthermore, it is responsible for 17% of the country’s gross value added in 2015-16, based on current prices and the 2011-12 data. India recently contributed for 7.8% of total world agricultural production, with the agricultural industry contributing 6.1% to the Indian GDP. India is a nation with a varied spectrum of cultural, ecological, and economic characteristics. The agricultural sector includes a wide range of production patterns and operational tasks. This study is qualitative in character and descriptive in form, using theorical analysis to investigate the marketing strategy of the agricultural industry in the rural parts of India. According to the findings of various research, the absence of small-scale farmers in supply chain channels may be due to a lack of information regarding storage practises and facilities. They had no idea how much their crops would yield, how to properly store and preserve them, how to assess and maintain their quality, or anything else.